Interior Hotel Resort Rembangan di Kabupaten Jember - Okdiyanto, Priskila (Intra, 2014)
Jember is a regency that have a lot of tourism objects and culture that needs to be introduced through Indonesia. Rembangan is one of potential tourism object that needs to be managed. This Unique Dutch Heritage Architecture and InteriorÂ  Building is historical. Based on research, Rembangan has been experienced some renovation for a few times, but Rembangan itself had not has a fixed form of building. Jember is famous with a fertile soil and abundant agriculture which becomes one of appeal tourism attraction. The peopleâs modern lifestyle has also required a changing of the activities pattern and interior needs, which caused there is a needs of facility replenishment that gives comfort and gratification. The facility will not only focus on its function but also from the aesthetic and culture application. The coherency of the function, aesthetic and culture will create an appropriate living environment. The concept application âLuxury in Farmingâ that gives luxury and farming environment which also the constitute of the soul of the Jember resident to applied in a space create a Rembangan tourism object will be the best hostelry in Jember town.